2013
DOI: 10.11622/smedj.2013049
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparison of chronic primary angle-closure glaucoma versus primary open-angle glaucoma in Singapore

Abstract: the optic disc, visual field and ocular characteristics (such as intraocular pressure [IOP] at presentation, best-corrected visual acuity, sphere equivalent, mean keratometry, axial length, lens thickness, corneal thickness and lens opacity) of a consecutive cohort of Asian patients with CPACG, and to compare them with a similarly enrolled sample of patients with POAG. METHODSThis was a prospective comparative study of new patients with POAG or CPACG, who presented to the National University Health System, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
3
12
2
1
Order By: Relevance
“…This result is in contrast with several studies on APAC patients where a reduction in the neuroretinal rim area was recorded [11,12]. For example, Shen SY et al have suggested a decrease in rim area 16 weeks after APAC in a predominantly Chinese population [11], accompanied by a reduction in disc area (10%).…”
Section: Hrt Evidence Of Damagecontrasting
confidence: 64%
See 1 more Smart Citation
“…This result is in contrast with several studies on APAC patients where a reduction in the neuroretinal rim area was recorded [11,12]. For example, Shen SY et al have suggested a decrease in rim area 16 weeks after APAC in a predominantly Chinese population [11], accompanied by a reduction in disc area (10%).…”
Section: Hrt Evidence Of Damagecontrasting
confidence: 64%
“…In this study, however, the ONH assessment was performed using optic disc photography. Similarly, Chai et al, in a case report, documented a reduction in rim area in a 64-year-old man one year after a single episode of APAC (2.15 mm 2 at 1 week, and 2.08 mm 2 at 1 year) [12,13]. The discrepancy with the literature could be due to the use of different imaging techniques for ONH assessment and on different study populations.…”
Section: Hrt Evidence Of Damagementioning
confidence: 91%
“…The few existing studies characterizing VF defect patterns associated with CACG suggest more generalized VF loss and less paracentral VF involvement in CACG than in POAG, as well as increased susceptibility to superior than inferior VF loss. [91][92][93][94][95] There may be particular need for better future characterization of patterns of CACG presentation in racially heterogeneous populations, as most previous research characterizing CACG-related VF defect patterns has focused on Asian patient populations, in whom CACG is known to be highest in prevalence.…”
Section: Section 42 Findings That Have Not Been Previously Reportedmentioning
confidence: 99%
“…25,26 Previous studies have reported that POAG and PACG have different patterns in visual field (VF) damage. [27][28][29][30][31] The VF damage is more pronounced in the superior hemifield than in the inferior hemifield in both POAG and PACG groups [32][33][34][35] ; however, this tendency is more obvious in POAG eyes. [27][28][29][30] Without doubt, the assessment of the rate of VF loss is very important in the management of glaucoma.Nonetheless, most of the previous studies have investigated the cross-sectional spatial patterns of VF loss.…”
mentioning
confidence: 99%